A new wind tunnel facility dedicated to sports technology research and development - Bäckström, M.; Carlsson, P.; Danvind, J.; Koptyug, A.; Sundström, D.; Tinnsten, M. (Procedia Engineering, 2016)
It is desirable to test sportswear and sports equipment at exactly the same conditions experienced during use. Although outdoor tests are in many cases the most adequate, they are at the same time quite complex, demand special measurement technology and wearable equipment. Results of such tests are often hard to interpret due to large variations because of rapidly varying ambient conditions and individual specifics of human objects, among other factors, which are hard or impossible to control. One common alternative is provided through indoor tests made in a stable, controlled environment.